2014
DOI: 10.1016/j.jinsphys.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Transport of H+, Na+ and K+ across the posterior midgut of blood-fed mosquitoes (Aedes aegypti)

Abstract: Mosquitoes pose significant threats to human health because they act as vectors for disease causing viruses and protozoans. Indeed, Aedes aegypti is known as the Yellow Fever Mosquito because of its role as a vector for viral infections that kill thousands of people each year. A more thorough understanding of mosquito physiology will aid development of novel control strategies. Previous work on ion transport across the midgut has been focused primarily on larval A. aegypti, while research on the midgut of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…The inhibition of Kir channels in Malpighian tubules is expected to disrupt the processing of blood meals by limiting the excretion of blood-derived electrolytes and water that are absorbed into the hemolymph. In addition, potential effects on the midgut’s digestion of blood and absorption of ions/fluid from the blood cannot be ruled out given that the mosquito midgut is a site of Kir mRNA expression and barium-sensitive K + transport283738. Our experiments in An.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of Kir channels in Malpighian tubules is expected to disrupt the processing of blood meals by limiting the excretion of blood-derived electrolytes and water that are absorbed into the hemolymph. In addition, potential effects on the midgut’s digestion of blood and absorption of ions/fluid from the blood cannot be ruled out given that the mosquito midgut is a site of Kir mRNA expression and barium-sensitive K + transport283738. Our experiments in An.…”
Section: Discussionmentioning
confidence: 99%
“…We used molecular phylogenetics, data mining of transcriptomes, molecular biology, and immunohistochemistry to characterize AeCA9 as a soluble cytoplasmic protein in the adult and larval alimentary canal. This work gives greater resolution to the mechanisms of pH regulation and proton transport from past studies [3,32]. Del Pilar Corena et al [3] suggested that CAs play a role in pH regulation of the gut, and these current studies show that AeCA9 is one of the CAs found in the gut tissues.…”
Section: Discussionmentioning
confidence: 53%
“…We hypothesize that the products of AeCA9 activity play roles in pH regulation, fluid secretion, and amino acid transport [23,48]. This hypothesis is adapted from the model proposed by Pacey and O′Donnell [32]. AeCA9 may provide H + for the transepithlial potential established by H + V-ATPase, which drives the displacement of ions across biological membranes for pH and ion regulatory processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti is an invasive species in the Americas, preferring areas close to humans where blood is easily accessible (Powell and Tabachnick 2013). After a female takes a blood meal into their midgut, the blood proteins are enzymatically digested into amino acids, which are then released into the hemolymph (Pacey and O'Donnell 2014). The accumulated amino acids in the hemolymph are absorbed by the mosquito fat body, functionally similar to the vertebrate liver, which synthesizes yolk protein precursors (YPP), called vitellogenin.…”
Section: Introductionmentioning
confidence: 99%